Factors that influence breastfeeding for babies aged less than 6 months at the Jagakarsa District Health Center, South Jakarta - Antaria, Abdullah (Universitas Aisyah Pringsewu, 2024)
In Indonesia, especially in rural areas, we often see supplementary feeding starting a few days after the baby is born. This habit is not good because giving additional food early can result in babies suffering from diarrhea more often, being easily allergic to certain food substances (7.5%), malnutrition or impaired child growth, decreased breast milk production.The aim of this study is to determine the factors that influence breastfeeding for babies aged less than 6 months at the Jagakarsa sub-district health center, South Jakarta in 2023.The survey design uses a cross sectional approach, namely the dependent variable and the independent variable are measured at the same time. The population in this study were all mothers who had babies aged less than 6 months in the Jagakarsa subdistrict health center, South Jakarta in 2023. Meanwhile, the sampling technique uses accidental sampling.The research results show the distribution of the frequency of breastfeeding for babies aged less than 6 months, where there are 44 mothers who breastfeed (64.9%), 45 mothers who have higher education (81.8%), 45 mothers who work. 40 people (97.6%), 55 people (78.6%) who did not receive family support, 49 people (70%) who received social support, 61 mothers who received husband support (87.1%) . There is a significant relationship between education (Pv = 0.015 with an OR of 0.194), employment (Pv = 0.000 with an OR of 56.667), and breastfeeding for babies aged less than 6 months. Meanwhile, the relationship that is not significant is social support (Pv= 1,000 with an OR of 00.865), husband's support (Pv=0.074 with an OR of 4.615), and family support (Pv=0.078 with an OR of 0.286).The analysis shows that several factors influence breastfeeding in babies aged less than 6 months. More recommended for parents/mothersIt is hoped to increase knowledge about breast milk through various sources of information. Keywords: Giving breast milk to babies aged less than 6 months.